1991
DOI: 10.2466/pms.1991.72.3c.1203
|View full text |Cite
|
Sign up to set email alerts
|

Mood Alterations with a Single Bout of Physical Activity

Abstract: Although numerous studies have examined the relationship among affect, personality, and physical activity, results are equivocal. Critics have cited inadequate experimental designs and analyses as the bases for ambiguity. This study addressed two identified weaknesses, length of exercise regimen and improper selection of subjects. Subjects were 72 college-age students who participated in one of three 75-min. activity classes (running, karate, weight lifting) and a lecture class (control subjects). The Profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…71 Another study also reported no significant changes in PWB. 50 A combination of aerobic and resistance exercise decreased PD by 20%. 56 Comparing aerobic exercise with resistance exercise yielded no significant changes in PD 71 ; however, another aerobic and resistance comparative study reported PD to decrease 25% in all modes of exercise compared with control.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…71 Another study also reported no significant changes in PWB. 50 A combination of aerobic and resistance exercise decreased PD by 20%. 56 Comparing aerobic exercise with resistance exercise yielded no significant changes in PD 71 ; however, another aerobic and resistance comparative study reported PD to decrease 25% in all modes of exercise compared with control.…”
Section: Resultsmentioning
confidence: 97%
“…29,30 One study used a combination of aerobic and resistance exercise, 56 and 2 studies compared the effects of acute aerobic exercise versus the effects of acute resistance exercise. 50,71 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of exercise modes including weight lifting (O'Connor, Bryant, Veltri, & Gebhardt, 1993), yoga 264 B. M. MILLER ET AL. (Berger & Owen, 1988, tai chi (Jin, 1989), short walks (Thayer, 1987), and running (Dyer & Crouch, 1988;McGowan, Pierce, & Jordan, 1991) demonstrate mood-regulating effects.…”
mentioning
confidence: 98%
“…For example, Szabo and colleagues collected post-exercise affective data from 174 habitual exercisers who engaged in their normal amount of aerobic dance, weight training, tai-chi or Hatha yoga (Szabo, Mesko, Caputo, & Gill, 1998). Similar designs were utilized by Dyer and Crouch (1988), Owen (1988), andMcGowan andcolleagues (1991); all of whom supported differences in psychological states as a function of exercise mode. For example, participants in one study were students voluntarily enrolled in swimming (n = 21), body conditioning (n = 16), coeducational fencing (n = 20), yoga (ns = 37, 26), a health science lecture (n = 35), or a physical education lecture (n = 15), who completed one class session in conjunction with psychological assessment (Berger & Owen, 1988).…”
mentioning
confidence: 99%